2016
DOI: 10.1002/iub.1581
|View full text |Cite|
|
Sign up to set email alerts
|

Association of plasma arginine with breast cancer molecular subtypes in women of Liaoning province

Abstract: Arginine is one of the human nonessential amino acids critical for the growth of human cancers. The aim of this study is to investigate the variation of arginine between breast cancer (BC) patients and benign mammary gland disease (control) patients to determine its value in predicting the risk of BC. We also explore the associations between arginine levels and breast cancer subtypes. Preoperative blood samples were obtained from 267 patients (102 BC and 165 controls) in 2015. Plasma arginine values were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Therefore, arginine plays an important role in the development of tumors. Hu et al reported that arginine is related to the molecular typing of breast cancer ( 11 ), and Selvi et al reported that arginine and its metabolites can assist the diagnosis of prostate cancer ( 10 ). In other tumors, arginine levels are generally decreased in the cancer group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, arginine plays an important role in the development of tumors. Hu et al reported that arginine is related to the molecular typing of breast cancer ( 11 ), and Selvi et al reported that arginine and its metabolites can assist the diagnosis of prostate cancer ( 10 ). In other tumors, arginine levels are generally decreased in the cancer group.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine and these downstream substances are involved in tumor growth, proliferation, invasion, metastasis and angiogenesis. In recent years, it has been reported that arginine is a sensitive marker for the development of breast cancer, prostate cancer and other tumor species ( 10 , 11 ). Abnormal expression of arginine in gastric cancer models has been found in cell and animal experiments ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the clinic, serum amino acid levels are usually used as nutritive index. With the deepening understanding of metabolites, serum amino acid levels are more and more used as disease biomarkers . Other research has focuses on serum amino acids changes in patients with various kidney diseases including drug‐induced nephrotoxicity and chronic renal failure …”
Section: Introductionmentioning
confidence: 99%
“…With the deepening understanding of metabolites, serum amino acid levels are more and more used as disease biomarkers. [9][10][11][12][13][14][15][16] Other research has focuses on serum amino acids changes in patients with various kidney diseases including drug-induced nephrotoxicity 17,18 and chronic renal failure. [19][20][21] Here, we investigated how changes in serum amino acid levels correspond to stages of renal function impairment with the aim of identifying more sensitive, accurate, and convenient serum biomarkers for early detection of chronic kidney disease.…”
mentioning
confidence: 99%
“…TNBC has the lowest arginine levels when compared to the other molecular subtypes. These findings suggested that a low arginine level was linked to the development of BC (Hu et al, 2016) suggesting that arginine deprivatio n using human recombinant arginase (e.g. HuArgI(Co)-PEG5000) could be a strategic therapeutic intervention in triple-negative breast cancer.…”
Section: Huargi(co)-peg5000 Decreases Focal Adhesions Formation In Hu...mentioning
confidence: 99%